Antioxidant and antimicrobial potential of stingless bee, (Heterotrigona itama) by-products - Md Akhir, Rabieatul Adawieah; Abu Bakar, Mohd Fadzelly; Sanusi, Shuaibu Babaji (Penerbit Akademia Baru, 2018)
Bee bread is the pollen that has been stored in the cells of the honeycomb with various enzymes and honey, which undergoes lactic acid fermentation, while propolis is a resinous material collected by bees from buds of the plants and transform it using bee enzymes. The main objective of this research was to investigate the antioxidant and antimicrobial activity of the stingless bee bread and propolis extracted using 70% ethanol and n-hexane. The antioxidant activity of sample extracts were determined by 2,2,-di-phenyl-2-picryl-hydrazyl (DPPH), 2,2-azinobis-(3-ethylbenzothiazoline-6- sulphonic acid) (ABTS) and Ferric Reducing Antioxidant Power (FRAP) assays while for the antimicrobial activity, the sample extracts were analyzed using disc diffusion and broth macrodilution assay. For the DPPH and ABTS assays, the results showed that ethanolic extract of bee bread showed the highest percentage of free radical scavenging as compared to other samples with the values of 93.60 ± 0.03% and 97.95±0.01%, respectively. However, FRAP value for both hexanic extract samples, bee bread and propolis have the values of 0.85±0.0 mM FE/g and 0.87±0.00 mM FE/g respectively which were higher than ethanolic extract samples, 2.41±0.02 mM FE/g (bee bread) and 6.64±0.04 mM FE/g (propolis). For disc diffusion assay, the results showed that ethanolic extract of bee bread and propolis as well as hexanic extract of propolis were able to inhibit all tested bacteria in varying diameter of the inhibition zone. Broth macrodilution assay showed minimum inhibition zone (MIC) ranging from <6.67 to 33.33 µL/mL. As the conclusion, all of the samples in this study displayed antioxidant and antimicrobial effect but there are different in the degree of antioxidant and antimicrobial activity exhibited between each of the samples.